Bosnia and Herzegovina : Staff Report for the 2005 Article IV Consultations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Bosnia and Herzegovina's 2005 Article IV Consultation reports that inflation has stabilized at industrial country rates, anchored by the currency board. About half of activity is accounted for by the private sector and banks have been almost completely privatized to nonresidents. The fiscal system, though fractured, has delivered a fiscal consolidation of 8 percentage points of GDP in four years, taking the balance to a deficit of 0.6 percent of GDP in 2004.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet